On the Move : The Lives of Nomads - Kocienda, Genevieve (NewYork Cambridge University, 2014)
Nomads still live in parts of the world. Life on the move is challenging ! Explore the cultures of nomads and why they live this way.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Pre-Intermediate Level; Nomads